Discovery of a novel dipeptidyl boronic acid proteasome inhibitor for the treatment of multiple myeloma and triple-negative breast cancer. Issue 3 (2nd January 2019) - Lei, Meng; Feng, Huayun; Bai, Enhe; Zhou, Hui; Wang, Jia; Qin, Yanru; Zhang, Haoyang; Wang, Xueyuan; Liu, Zhaogang; Hai, Ou; Liu, Jia; Zhu, Yongqiang
Abstract : An effective candidate for the treatment of both MM and tri-negative breast cancer. Abstract : A series of novel dipeptidyl boronic acid compounds were designed, synthesized and biologically investigated for the inhibition of the β5 subunit of 20S proteasome and several compounds showed high activities with IC50 values of less than 10 nM. Some of these compounds potently inhibited the multiple myeloma (MM) cancer cell lines with IC50 values of less than 10 nM. It was reported that the inhibition of both β2 and β5 subunits strongly increased the cytotoxicity of proteasome inhibitors in solid tumor cells, so some of the compounds were evaluated for the inhibition of the β2 subunit and the solid tumor triple-negative breast cancer cell line MDA-MB-231. The results showed that three compounds were active for both the β2 subunit and the triple-negative breast cancer cell line MDA-MB-231. The in vivo pharmacokinetic results showed that compound8t had good biological parameters for both ig and iv administrations. An in vivo pharmacodynamic experiment showed that compound8t inhibited the β5 subunit in whole blood more greatly than the marketedMLN9708 with the same dose at different time periods. A pathological analysis indicated that the injection of compound8t in the tumor of a triple-negative breast cancer xenograft mice model led to tumor cell necrosis, nucleus condensation, deep staining, cell fragmentation, dissolution and neutrophil infiltration compared with the control group. The data in hand showed that compound8t might be an effective candidate for the treatment of both MM and triple-negative breast cancer.